Analisis kualitas udara menggunakan internet of things di pintu perlintasan kereta api - Kusumaningrum, Evy; Hermawan, Heru Bagus; Sumarsono; Hariyadi, Dedy (Universitas Muhammadiyah Riau, 2023)
The limited number of air quality sensors causes the presentation of Air Quality Index information to be not optimal. In principle, the installation of Air Quality Index sensors can provide input in air quality control and monitoring policies in an area. However, some places that have the potential to become local tourism or gathering places such as around the railroad crossing area do not have air quality sensors installed. Wind speed when trains pass can cause dust to scatter. Therefore, it is necessary to conduct further studies related to air quality around railroad crossings. Therefore, this research proposes to analyze and monitor air quality around railroad crossings in the Special Region of Yogyakarta based on the Internet of Things. In this study, the installed sensors functioned to monitor air quality at 3 locations that have different characteristics so that the data generated is also different. Based on the PM25 sensor, the air quality is categorized as Good 50% and Moderate 50%, while the PM10 sensor is categorized as Good 80% and Moderate 30%. The Internet of Things sensor built in this study is still not integrated in its recording between wind speed and air quality.